OLAM BIRLIGI VA AXLOQIY ONG: CHITTICK TALQINI ORQALI FARGHONIY KOSMOLOGIYASIGA YANGI YONDASHUV - Obidov, Asliddin (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
This paper reexamines Saʿid al-Din al-Farghani’s cosmology through William C. Chittick’s hermeneutic analysis. Farghani views waḥdat al-wujud not as abstract monism but as a cosmic order linking being to ethical responsibility. His commentary on Ibn al-Fariḍ presents the Muḥammadan Reality as the axis connecting divine manifestation with human vocation. The study highlights dhikr as a movement from ontological awareness to moral agency. Farghani’s thought thus offers a unified philosophical model in which ontology and ethics mutually reinforce one another.